Effectiveness of life enrichment and advancement program on improving emotional adjustment of women with M.S. - Ghasemzadeh, Azizreza; Saadat, Maryam; Rabbani Zadeh, Mansoureh (Psychology of Woman Journal, 2023)
This study aimed at determining the effectiveness of life enrichment and advancement program on emotional adjustment of women with M.S. It was a quasi-experimental study with experimental and control groups and pre-post-test design. Statistical population included women with M.S. referred to Loghman Hakim Hospital and Imam Khomeini Hospital. A sample of 30 women was randomly selected and assigned to experimental and control groups. The experimental group received 6 sessions of group intervention and the control group was on the waiting list. Both groups responded to Bell’s adjustment scale before and after the experiment. Descriptive statistics and co-variance analysis were used to analyze the data. The results showed that life enrichment and advancement program had an effect on emotional adjustment (F = 26/74), (P <0/001) so that it improved emotional adjustment in women with M.S.